2021
DOI: 10.3390/pharmacy9010014
|View full text |Cite
|
Sign up to set email alerts
|

Use of Concept Mapping to Identify Expectations of Pharmacy Students Selecting Elective Courses

Abstract: The objective of this study was to demonstrate the use of concept mapping as a method for analyzing pharmacy students’ qualitative perceptions of their expectations of elective courses and to thus help guide delivery methods and course content. A survey containing demographic, Likert scale, and open-ended questions was administered to second-year pharmacy students prior to the start of elective courses and an innovative methodology, concept mapping, was used to identify major themes relating to student expecta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Undoubtedly, pharmacy programs that already offered online classes were better positioned to transition more of their curricular components to an online setting during the COVID-19 pandemic based on their existing infrastructure and experience. Several educational research studies published before the COVID-19 pandemic have shown that online courses are generally well accepted by pharmacy students and that academic standards can be maintained when pharmacy courses are offered online [2][3][4]. For example, our group and others have demonstrated that more than 50% of pharmacy students taking elective courses preferred online delivery and that student satisfaction levels with online elective courses are high [2][3][4].…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…Undoubtedly, pharmacy programs that already offered online classes were better positioned to transition more of their curricular components to an online setting during the COVID-19 pandemic based on their existing infrastructure and experience. Several educational research studies published before the COVID-19 pandemic have shown that online courses are generally well accepted by pharmacy students and that academic standards can be maintained when pharmacy courses are offered online [2][3][4]. For example, our group and others have demonstrated that more than 50% of pharmacy students taking elective courses preferred online delivery and that student satisfaction levels with online elective courses are high [2][3][4].…”
Section: Introductionmentioning
confidence: 78%
“…The successful use of online delivery of didactic classes pre-pandemic and during the pandemic is well described in the literature for many types of higher education, including pharmacy education, with many students indicating high levels of satisfaction with online education [2][3][4][5][6][7][8]66]. As mentioned above, it would be helpful for future studies in pharmacy education to place more focus on the impact of online learning on student learning outcomes (in this scoping review, only one study assessed course scores and grades and showed no difference in performance).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Otherwise, the disadvantages of T&L in a DLE will come to the fore. They primarily relate to lower student engagement, limited interaction, lack of hands-on experience, interaction in discussions, and the integrity of exams administered online (Chen et al, 2020;Courtney et al, 2022;Dziuban et al, 2015;Ives, 2020;Pate et al, 2017;Porter et al, 2014;Shawaqfeh et al, 2020;Vinall & Balan, 2021). Indeed, online T&L was not a new concept in 2020, but since it was not extensively used by most universities, majority of teachers were not adequately trained nor familiar with the technological capabilities that can facilitate the learning process in the digital environment.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, 56% of pharmacy students declared that they preferred the online delivery of courses over in-person classes in a study, which was carried before the COVID-19 pandemic. In this study, the online delivery format was a key factor of students' choice of an elective course [15].…”
Section: Introductionmentioning
confidence: 99%